Philosophy of Education in the Digital Age: A Systematic Review of ELT Approaches and Ethical Considerations - Ganap, Nindy N.; Mogea, Tini (Journal of English Culture, Language, Literature and Education, 2024)
The rapid integration of digital technologies into English Language Teaching (ELT) has significantly reshaped pedagogical practices, offering both opportunities and ethical challenges. This study reviews the philosophy of education in the digital age, with a focus on ELT approaches and the ethical concerns arising from their adoption. Three key issues are identified: accessibility and the digital divide, data privacy and security, and reduced human interaction. These challenges underscore the importance of a balanced approach to digital education that upholds equity, security, and social connection. The findings reveal that, while digital tools enhance access to educational resources, they risk excluding students from marginalized communities due to technological disparities. Similarly, the growing use of digital platforms raises concerns about the collection and misuse of sensitive student data, emphasizing the need for robust data protection measures. Additionally, the decline in human interaction within virtual learning environments may affect student motivation, engagement, and emotional well-being. Addressing these ethical challenges is crucial to ensuring that digital ELT adheres to the principles of inclusivity and fairness, fostering a more equitable and secure learning environment for all students. This review provides practical insights for educators, policymakers, and stakeholders in navigating the complexities of digital education.